The Rational Choice of Outer Baduy People Choosing Non-Formal Education: Case Study at PKBM Kencana Ungu, Leuwidamar Village Lebak District - Hidayat, Rakhmat; Minarmi, Minarmi (Jurnal Sosiologi Pendidikan Humanis, 2023)
This research was conducted because there is a phenomenon of customary and educational dilemmas in the Baduy Tribe. The Baduy tribe has a usual prohibition for requiring their children to access formal education. This dilemma makes Non-Formal Education (PNF) an alternative mechanism for the Baduy Tribe to access education. The PNF was carried out through the existence of the Society Learning Center or Pusat Kegiatan Belajar Masyarakat (PKBM) Kencana Ungu. This paper explains two critical things. Firstly, it describes the learning culture of the Outer Baduy people in PNF at PKBM Kencana Ungu. Secondly, it tells the people of the Outer Baduy Tribe choosing PNF at PKBM Kencana Ungu from the perspective of rational choices. This research uses a qualitative approach with descriptive methods—the data is obtained through observation, interviews, and documentation. The researchers interviewed 12 informants in-depth, namely traditional leaders, the Head of PKBM Kencana Ungu, three (3) tutors from PKBM Kencana Ungu, and seven (7) people from the Outer Baduy Tribe who accessed education at PKBM Kencana Ungu. The research location was at the Kencana Ungu PKBM in Dukuh Village, Leuwidamar Village, Leuwidamar District, Lebak Regency. The conclusion of this paper shows that the learning culture of the Outer Baduy Tribe has changed from an oral culture that was passed down from generation to generation to a written culture. This change in learning culture causes changes in the behavior of the Outer Baduy Tribe towards customary arrangements. This change in learning culture causes changes in the conduct of the Outer Baduy Tribe towards everyday arrangements. In addition, the primary considerations for the Outer Baduy people accessing education at PKBM Kencana Ungu are rational choices based on a calistung learning culture, rational choices based on social status, and rational choices based on mindset. The rational choice theory used in this paper refers to James Coleman. These various preferences have various implications for several aspects of the life of the Outer Baduy people, namely educational implications, socio-cultural implications, economic implications, and psychological implications.  Pilihan Rasional Suku Baduy Luar Memilih Pendidikan Non Formal: Studi Kasus  di PKBM Kencana Ungu Desa Leuwidamar Kabupaten LebakPenelitian ini dilakukan karena ada fenomena dilema adat dan pendidikan di Suku Baduy. Suku Baduy memiliki larangan adat untuk mewajibkan anaknya mengakses pendidikan formal.  Adanya dilema tersebut menjadikan Pendidikan Non Formal (PNF) sebagai mekanisme alternatif bagi Suku Baduy untuk mengakses pendidikan. PNF tersebut dilakukan melalui keberadaan PKBM Kencana Ungu. Paper ini menjelaskan dua hal penting. Pertama, mendeskripsikan budaya belajar masyarakat Suku Baduy Luar pada PNF di PKBM Kencana Ungu. Kedua, mendeskripsikan masyarakat Suku Baduy Luar memilih PNF di PKBM Kencana Ungu dalam perspektif pilihan rasional. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data penelitian diperoleh melalui observasi, wawancara dan dokumentasi. Peneliti mewawancarai 12 informan secara mendalam, yakni tokoh pemimpin adat, Kepala PKBM Kencana Ungu, tiga (3) orang tutor PKBM Kencana Ungu dan tujuh (7) orang Suku Baduy Luar yang mengakses pendidikan di PKBM Kencana Ungu. Lokasi penelitian dilakukan di PKBM Kencana Ungu yang berada di Kampung Dukuh Desa Leuwidamar Kecamatan Leuwidamar, Kabupaten Lebak. Kesimpulan dari paper ini menunjukkan bahwa  budaya belajar pada Suku Baduy Luar mengalami perubahan dari budaya lisan yang didapatkan secara turun-temurun saat ini berubah menjadi budaya tulisan. Perubahan budaya belajar ini menyebabkan perubahan perilaku Suku Baduy Luar terhadap tatanan adat. Selain itu, pertimbangan dasar masyarakat Suku Baduy Luar mengakses pendidikan di PKBM Kencana Ungu yaitu, pilihan rasional berdasarkan budaya belajar calistung, pilihan rasional berdasarkan status sosial dan pilihan rasional berdasarkan pola pikir. Teori pilihan rasional yang digunakan dalam paper ini mengacu kepada James Coleman.Berbagai preferensi tersebut memberikan berbagai implikasi pada beberapa aspek kehidupan masyarakat Suku Baduy Luar, yaitu implikasi pendidikan, implikasi sosial budaya, implikasi ekonomi dan implikasi psikologis.